2016
DOI: 10.1063/1.4953491
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial diversity investigation in oil palm plantation using terminal restriction length polymorphism

Abstract: Abstract. Oil palms ((Elaeis guineensis Jacq.), have been widely cultivated in Sumatera for over two planting generations and occupied lands with various soil characteristics. In order to investigate microbial diversity in various soil characteristics of oil palm plantation, a molecular analysis called Terminal Restriction Length Polymorphism (T-RFLP) was adopted. The aim of this research was to analyze the bacterial diversity within several oil palm plantations in Sumatera. DNA extraction was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Thus, the presence of Catenibacterium (and to a lower extent some of other Firmicutes) is most likely associated with the intestinal microbiota of these mammal species [ 69 , 70 , 71 , 72 ]. However, we should point out that Catenibacterium has also been found in soils from oil palm plantations [ 73 ] and maritime soils of the southern Antarctic [ 74 ], highlighting the need for further studies concerning the ecosystem functions of these microbes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the presence of Catenibacterium (and to a lower extent some of other Firmicutes) is most likely associated with the intestinal microbiota of these mammal species [ 69 , 70 , 71 , 72 ]. However, we should point out that Catenibacterium has also been found in soils from oil palm plantations [ 73 ] and maritime soils of the southern Antarctic [ 74 ], highlighting the need for further studies concerning the ecosystem functions of these microbes.…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that the endemic soil is more susceptible to Ganoderma boninense. It is supported by another study that stated that Ganoderma boninense was elevated with a decline in the presence of indigenous beneficial bacteria [15]. In general, the changes in bacterial composition are more influenced by the agricultural An OTU table representing the occurrence of each OTU in each sample was utilized to make a heat map.…”
Section: Bacterial Community Structurementioning
confidence: 92%
“…Bahan organik merupakan sumber energi bagi biota tanah, dimana biota tanah memiliki peran penting terhadap banyak proses yang terjadi di dalam tanah termasuk penyerapan hara oleh tanaman (Ashton-Butt et al, 2018). Beberapa penelitian terdahulu melaporkan bahwa aplikasi bahan organik dapat meningkatkan diversitas dan kelimpahan dari mikroorganisme tanah seperti cacing tanah yang memiliki banyak manfaat untuk mendukung pertumbuhan tanaman (Carron et al, 2015a;2015b;Situmorang et al, 2014) Lebih lanjut Hal yang sama juga dilaporkan oleh Tao et al, (2016) yang menyatakan bahwa aplikasi TKS dapat meningkatkan aktivitas fauna tanah dan terjadi peningkatan kelimpahan makrofauna tanah termasuk semut, cacing tanah, dan beberapa jenis kumbang.…”
Section: Perbaikan Reaksi Biokimia DI Dalam Tanahunclassified